PERBANDINGAN VIABILITAS EMBRIO PASCA PENGHANGATAN PADA PROSEDUR VITRIFIKASI DENGAN MENGGUNAKAN GAMA SLEEVED CRYOLOOP 0,1 Î¼l DAN CRYO-STRAW SEBAGAI ALAT (DEVICE) (MODEL MENCIT - , LARA MAISHA; , Prof. dr. Djaswadi Dasuki, MPH, PhD, SpOG(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction. The number of embryo in vitro fertilization should be controlled before being transferred back into the uterus to prevent the occurrence of multiple gestation. The excess embryo can be stored by vitrification method. The device which is used to store the embryo is one of important factor in maintaining the viability of the embryo. Objectives. Comparing the use of gama sleeved cryoloop 0.1 mL to 250 mL cryo-straw in maintaining the viability of embryos in vitrification procedures. Method. This research is an experimental study. Mice embryos derived from female Swiss Albino mice were 6-8 weeks old that has been stimulated. 8-cell stage embryos vitrified then at least for 24 hours using a device